Effect of probiotics on the growth, blood profile, and nutritional-metabolic profile of feedlot cattle - Flavia I. Mansilla; María C. Aristimuño Ficoseco; María H. Miranda; Marcela D’Urso Villar; Graciela M. Vignolo; María E. F. Nader-Macías (Academia Biology)
The blood profile, nutritional-metabolic status, and growth performance of cattle receiving probiotic lactobacilli for 105 days from entry to a feedlot system were evaluated. The trial involved 60 Brangus/Braford castrated steers. They were randomly allocated in pens (n = 15/treatment) and in-feed supplemented with different probiotic suspensions (107–108 CFU/mL/day). The suspensions consisted of (A) Lactobacillus acidophilus CRL2074, (B) Limosilactobacillus fermentum CRL2085, or (C) multistrain CRL2074 + CRL2085 + Limosilactobacillus mucosae CRL2069 formulations, against the control group. Individual samples were taken from each animal thrice throughout the assay (0, 45, and 105 days). Analysis of clinical parameters showed optimal animal body condition and sensorium state. Isolated nasal discharges and the absence of diarrhea were observed at 105 days in the group administered with multistrain and Lim. fermentum CRL2085 probiotics. An increasing trend was observed in cattle growth throughout the trial, which was calculated based on the height at the withers and the thoracic diameter. Weight increase and daily weight gain (1.31 ± 0.12 kg and 1.21 ± 0.21 kg/day, respectively) were maximum for cattle supplied with CRL2085 and multistrain probiotics. Blood and serum parameters were within referential ranges for the control and probiotics-supplemented groups; however, mean values of hematocrit were higher, while the serum glucose, lipid profile, and C-reactive protein values were lower in all the groups. In addition, the multistrain probiotic formulation exhibited higher numbers of cultivable lactic acid bacteria and a slight decrease in the number of enterobacteria in feces at the end of the trial. Therefore, there is great potential for multistrain probiotic formulation to improve the overall performance of feedlot beef cattle.